COMPARISON OF NUTRITIONAL STATUS IN NORMAL PREGNANT WOMEN AND KEK PREGNANT WOMEN AT ULEE KARENG COMMUNITY HEALTH CENTER, BANDA ACEH CITY - Safila, Lili; Amin, Fauzi Ali; Agustina, Agustina; Arlianti, Nopa (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: The nutritional status of pregnant women is one of the indicators in measuring the nutritional status of the community. If the nutritional intake for pregnant women from food is not balanced with the body's needs, there will be a nutritional deficiency. As a result, it can cause maternal death caused by bleeding due to nutritional anemia and Chronic Energy Deficiency (CED) during pregnancy. In Aceh province in 2017, pregnant women at risk of CED increased by 0.6% from the previous year, which was 8.7%. The highest risk of CED occurred at the Ulee Kareng Health Center, which in 2017 was 33 people (5.31%). The purpose of this study was to determine the comparison of nutritional status in normal pregnant women and CED at the Ulee Kareng Health Center, Banda Aceh City. Method: This study was conducted using a comparative study method with a Case Control design. The population in this study were all pregnant women who experienced KEK as many as 30 people and those who did not experience KEK as many as 30 people. Sampling used the Purposive Sampling technique. Data collection was carried out using a questionnaire with an interview technique. Data analysis used T-Test test. Result: The results showed that there were differences in food intake (p value = 0.0015) and knowledge of nutrition during pregnancy (p value = 0.001) with nutritional status in normal pregnant women and KEK. There was no difference in pregnancy spacing (p value = 0.217), parity value (p value = 0.503) with nutritional status in normal pregnant women and KEK. Food intake and knowledge factors were the variables that most influenced the differences in nutritional status of normal pregnant women and KEK. Recommendation: It is hoped that health centers will be able to provide counseling and information about nutritious food for pregnant women so that they do not experience KEK.